Degradation and sorption of fipronil and atrazine in Latossols with organic residues from sugarcane crop - Raquel de Oliveira Silva; Rômulo Penna Scorza Júnior; Maricy Raquel Lindenbah Bonfá; Maria Fernanda Zaneli Campanari; Ieda de Carvalho Mendes (Ciência Rural, 2016)
ABSTRACT: Organic residues from sugarcane crop and processing (vinasse, boiler ash, cake filter, and straw) are commonly applied or left on the soil to enhance its fertility. However, they can influence pesticide degradation and sorption. The objective of this study was to assess the effect of adding these organic residues on the degradation and sorption of fipronil and atrazine in two soils of the State of Mato Grosso do Sul, MS, Brazil. The degradation experiment was carried out with laboratory-incubated (40 days; 28°C; 70% field capacity) soils (0-10cm). The batch equilibration method was used to determine sorption. Fipronil (half-life values of 15-105 days) showed to be more persistent than atrazine (7-17 days). Vinasse application to the soil favored fipronil and atrazine degradation, whereas cake filter application decreased the degradation rates for both pesticides. Values for sorption coefficients (Kd) were determined for fipronil (5.1-13.2mL g-1) and atrazine (0.5-1.5mL g-1). Only straw and cake filter residues enhanced fipronil sorption when added to the soil, whereas all sugarcane residues increased atrazine sorption.